THE CORRELATION OF INTERNATIONAL PROSTATE SYMPTOM SCORE (IPSS) WITH QMAX ON UROFLOWMETRY OF BENIGN PROSTATIC HYPERPLASIA (BPH) PATIENTS AT ABDUL WAHAB SJAHRANIE HOSPITAL IN SAMARINDA - Nia Ramadhanurrosita; Boyke Soebhali; Hary Nugroho (Jurnal Ilmu Kesehatan, 2019)
Background: Benign prostatic hyperplasia (BPH) is one of the most common benign tumors on elderly man. BPH manifests as lower urinary tract symptoms (LUTS). To determine subjectively the symptom severity of LUTS, quantitatively, it was used a diagnostic tool called IPSS. However, IPSS individually is not enough in enforcement of definitive diagnosis man with LUTS. There were some other diagnostics tools used in diagnosing BPH, the other one is uroflowmetry examination that is objective. This research aims are to know the correlation between IPSS and Qmax on uroflowmetry in BPH patients at Abdul Wahab Sjahranie Hospital in Samarinda.Methods: This research is an analytic survey with observational design, cross sectional. The subject of this research is BPH patients with LUTS at Abdul Wahab Sjahranie Hospital in Samarinda on March until May 2019. Data is collected primarily through the IPSS’s questionnaire filled by the patient. Data flow rate obtained through uroflowmetry examination with emphasis on maximum flow rate (Qmax).Results: This research found that BPH is majorly found on group age 60-69 years (45%). IPSS with moderate symptom severity mostly found on patient (60%). Nocturia (90.5%) and incomplete emptying (85%) is the most frequent symptoms found. The analysis results showed that IPSS had a moderate negative correlation with Qmax on uroflowmetry (r = -0,567; p = 0,009).Conclusions: There was correlation between IPSS and Qmax on uroflowmetry of BPH patients at Abdul Wahab Sjahranie Hospital in Samarinda.